Assessment of natural radionuclides at Kinta River, Malaysia: relationship between the turbidity to uranium and thorium concentrations - Selamat, Siti Syafika (2015)
This study aims to investigate the relationship between the turbidity to uranium and thorium concentrations. Since the radionuclides analysis is complex and time consuming, turbidity monitoring on river is proposed to be an indirect indicator for uranium and thorium concentration. Eighteen water samples were collected and turbidity measurements were conducted at several locations from Kinta River. The concentration of uranium and thorium were analyzed using inducted coupled plasma mass spectrometer (ICP-MS). The concentrations of thorium were varied from 44 ng L?1 to 787 ng L?1 while the concentration of uranium varied from 45 ng L?1 to 371 ng L?1. Statistical analyses were applied to determine the relation between turbidity and concentrations of uranium and thorium at Kinta River. The correlation coefficients (R) show a strongly correlation, with R values of 0.915 and 0.881 for turbidity with concentrations of uranium and thorium, respectively.